Perencanaan ulang tata letak gudang PT. XYZ menggunakan metode Class Based Storage dan Systematic Layout Planning - Syah, Mochammad Dhia Najmuddin; Islami, Mega Cattleya Prameswari Annissaa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Optimal warehouse layout planning plays an important role in improving operational efficiency and productivity of a company. PT XYZ faces problems in the form of an unorganized warehouse layout, causing increased search time for goods and material movement. This study aims to redesign the warehouse layout by applying the Class Based Storage (CBS) and Systematic Layout Planning (SLP) methods. The CBS method is used to classify products based on the level of goods turnover (fast-moving, medium-moving, and slow-moving), while the SLP method helps redesign the layout by considering material flow and operational activities. The results of the study indicate that the application of both methods succeeded in designing a more organized warehouse layout, reducing material movement distance, and minimizing search time for goods. Thus, the combination of the Class Based Storage and Systematic Layout Planning methods can be used as an effective approach to improving warehouse governance at PT XYZ.